Introgressing resistance to fusarium root rot in selected farmer preferred Andean bean genotypes from Meso-American line and mapping of associated resistance quantitative trait loci - Kamfwa, Kelvin (Makerere University, 2010)
The common bean (Phaseolus vulgaris L.) is a primary protein source in the diet of many low-income populations worldwide. Bean root rots have been reported to occur in most bean fields throughout the world. In Uganda, bean root rot is one of the major constraints to bean production, with that caused by Fusarium solani (Mart.) f.sp. phaseoli (Burkholder) (N.C. Snyder & H.N. Hans) resulting in substantial yield losses. The use of resistant varieties is probably the most effective control measure against Fusarium root rot, especially for small-scale farmers with limited access to fungicides. Sources of resistance to Fusarium root rot exist in common beans and have been reported to occur in Africa. Most of the developed and identified resistant genotypes are either late-maturing and small or black-seeded, with a climbing growth habit. None of the commercial Andean bean varieties currently grown in Uganda are resistant to this pathogen. Genetic resistance to Fusarium root rot is polygenic and is strongly influenced by environmental factors. Response to selection for quantitative traits, such as root rot resistance, is slow due to the genetic complexity of the trait and the difficulty in evaluating resistance. Indirect selection for Fusarium root rot resistance based on genetic markers linked to the quantitative trait loci (QTL) for resistance would facilitate improvement, given the limitations of field selection, which are expensive, not consistent across environments and require destructive sampling. The overall objective of this study was to develop approaches based on quantitative trait loci for improving resistance in common beans to Fusarium root rot. The specific objectives were: (i) to confirm the usefulness of a Meso-american source (MLB 49-89A) in transferring resistance to Fusarium solani f.sp. phaseoli into locally adapted Andean types (K20 and K132); (ii) to identify quantitative trait loci that condition resistance to Fusarium root rot in common beans. Two populations of 90 and 78 F4:5 recombinant lines from K20 x MLB-49-89A and K132 x MLB-49-89A respectively, were used to confirm the usefulness of a Meso-american source (MLB 49-89A) in transferring resistance to Fusarium solani f.sp. phaseoli into locally adapted Andean types (K20 and K132). Both K20 and K132 are susceptible to Fusarium root rot, while MLB-49-89A is resistant. The two populations and their parents were evaluated for Fusarium root rot in a screenhouse using a randomised complete block design with two replications in wooden trays measuring 0.74 x 0.42 x 0.115 m. The K20 x MLB-49-89A population was skewed toward resistance while K132 x MLB-49-89A was skewed toward susceptibility. These results therefore clearly show differences in parental effects of K20 and K132 on the resistance to Fusarium root rot. Such differences in means and distributions between the two populations suggest that K20 possesses one or more genes that interact in an epistatic manner with two or more resistance loci in MLB-49-89A. In contrast, K132 apparently lacks the beneficial allele that is present in K20, or has an alternate allele that enhances susceptibility. The frequency distributions for both populations were bimodal, suggesting that a major gene was involved in resistance. A number of lines that had very good resistance levels to Fusarium root rot were identified from both populations. Both the narrow and broad sense heritabilities obtained for K132 x MLB-48-89A in this study were very high (h2B=0.99; h2N=0.98, referenced to additive variance in the F2, reported on a line-mean basis from 2 replications). On the same basis, heritability estimates in K20 x MLB-48-89A were also high (h2B=0.86; h2N=0.81). The heritability estimates obtained in this study and in previous studies by Mukankusi (2007) indicate that improvement of the Andean varieties for resistance to Fusarium root rot using the Meso-american line MLB-49-89A should be possible. The results of this study have shown that when when using MLB-49-89A, it would be easier to improve K20 than K132 for Fusarium root rot resistance. The cross of K132 x MLB 49-89A was emphasized for the mapping study. A total of 35 SSR markers were screened for polymorphism in the parents. Fifteen of the 35 SSR markers were polymorphic, representing 42% of the tested SSR markers. Twelve of the SSR markers gave clearly distinguishable bands and were therefore used for analysis. A mapping population of 62 F4:5 recombinant inbred lines of K132 x MLB 49-89A was used for identifying quantitative trait loci conditioning resistance to Fusarium root. A linkage map was constructed by placing nine of the polymorphic SSR markers into three partial-linkage groups, each with three SSR markers. The other three markers did not connect to these three linkage groups. Using single marker analysis, two SSR markers that were closely linked to each other (PVBR87 and PVBR109) were significantly associated with Fusarium root scores (p<0.0001) in K132 x MLB-49-89A population. Another SSR marker, PVBR255, showed significant effects on Fusarium root rot scores, but at a reduced significance level (p≤0.05). The other nine SSR markers showed no significant effects. Composite interval mapping detected a major QTL in K132 x MLB-49-89A population between PVBR87 and PVBR109 with a LOD score of 6.1 and coefficient of determination (R2) of 34% and did not assign independent significance to the distantly-liked marker, PVBR255. Therefore, only one QTL was detected in the present study, but it is a major QTL, as indicated by the large R2. The two markers associated with the QTL (PVBR87 and PVBR109) are found on linkage group B3 of the common bean core map, close to the region where resistance to root rots, anthracnose, common bacterial blight and bacterial brown spot have been previously mapped. Only four SSR markers (PVBR87, PVBR109, BM156 and BM172) were used in the K20 x MLB 49-89A population because of resource constraints. The two SSR markers (PVBR87 and PVBR109) that were significantly associated with Fusarium root rot resistance in K132 x MLB-49-89A population, also showed significant associations (R2 = 14%, P < 0.001) in the K20 x MLB-49-89A population. This is a confirmation of the presence of a QTL identified on linkage group B3 close to these two markers in the K132 x MLB-49-89A population. The association of this major QTL with resistance in both populations suggests that this QTL may be useful more broadly. There is need to determine whether this QTL is also present in different sources of resistance and whether the two associated SSR markers are useable for marker-assisted selection in a wider range of materials. Fine-resolution mapping could be achieved by using additional markers near the identified markers, enhancing the efficiency of marker-assisted selection and revealing whether this is indeed a single QTL or whether it is made up of several linked QTL, each with a small effect. The detection of this major QTL for resistance to Fusarium provides good prospects for using QTL--based approaches to introgress resistance to Fusarium root rot from Meso-american genotypes into locally adapted Andean bean genotypes.